2009
DOI: 10.1177/154193120905301850
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Model of Human-Automation Interaction

Abstract: Why is it important to understand human behavior in automated environments? The performance of a humanautomation system is a product of the quality of the support provided by the automation and the manner in which that support is used by the human. Therefore, the solution to reaching an optimal level of system performance does not lie exclusively within possible improvements to technological components, but also by understanding the interaction of humans with automated agents. A conceptual model of human-autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…In both Experiment 1 and Experiment 2, levels of expectation directly matched initial expectations of automation reliability. Perceived reliability is also presumed to predict or even mediate automation use (e.g., Bustamante, 2009;Merritt & Ilgen, 2008;Sanchez, 2009;Wiczorek & Manzey, 2010); however, our findings did not show this relationship.…”
Section: Perceived Reliabilitycontrasting
confidence: 97%
See 3 more Smart Citations
“…In both Experiment 1 and Experiment 2, levels of expectation directly matched initial expectations of automation reliability. Perceived reliability is also presumed to predict or even mediate automation use (e.g., Bustamante, 2009;Merritt & Ilgen, 2008;Sanchez, 2009;Wiczorek & Manzey, 2010); however, our findings did not show this relationship.…”
Section: Perceived Reliabilitycontrasting
confidence: 97%
“…Another factor that influences dependence on automation is users' perceptions of the automation, including perceived reliability. This factor presumably mediates actual automation reliability and the human's use of the automation (e.g., Merritt & Ilgen, 2008;Sanchez, 2009). However, other studies have shown that perceptions do not mediate, but rather predict, automation use (e.g., Bustamante, 2009;Wiczorek & Manzey, 2010).…”
Section: Role Of Perceptions and Expectationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The literature distinguishes among extrinsic and intrinsic factors regarding trust in automation [32]. An important extrinsic factor is the workload of operator (more workload generally implies more trust in automation) [208], whereas an intrinsic factor that must be remarked is the operator selfconfidence (less self-confidence implies more trust in automation) [208]. The experiments show the operators have more confidence with low autonomy systems than with high autonomy ones, this difference is bigger when the number of robots is higher, and the presence of failures has a remarkable influence on this perception [201].…”
Section: Trust In Automationmentioning
confidence: 99%